Pengaruh Product Ingredients, Brand Ambassador dan Social Media Marketing terhadap Keputusan Pembelian Produk Viva Cosmetics di Kota Bandung - Ayu Indah; Indri Ferdiani Suarna (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Cosmetic products have recently become very close to the community and have even become a major need for most women. The magnitude of this cosmetic need causes competition between cosmetic manufacturers. The purpose of this study was to determine the effect of Product Ingredients, Brand Ambassadors, and Social Media Marketing on Purchasing Decisions for Viva Cosmetics Products in Bandung City. The type of research used is descriptive and verification with an approach using quantitative methods, with data distribution techniques using a questionnaire. The results of respondents' answers to the questionnaires distributed, then the research instrument analysis, clasi assumption test, and multiple linear regression will be carried out. Statistical analysis tools in this study used Statistical Package for the Social Science (SPSS) software. The number of samples in this study were 385 people, by determining the sample using simple random sampling. Based on the results of the t test in this study, it shows that partially Product Ingredients, Brand Ambassadors, and Social Media Marketing have a positive and significant influence on Purchasing Decisions. Simultaneously Product Ingredients, Brand Ambassadors, and Social Media Marketing have a positive and significant influence on Purchasing Decisions. The results showed that Product Ingredients, Brand Ambassadors, and Social Media Marketing had an influence of 39.1% on Purchasing Decisions while the remaining 60.9% was influenced by other variables not examined in this study.